Helicobacter pylori and gastric cancer - Živković-Perišić Snežana V. (Srpsko lekarsko drustvo, 2020)
Introduction: According to GLOBOCAN estimates for 2018, gastric cancer was the fifth most common cancer and the third most common cause of death from malignant diseases in the world. Although the etiology of this cancer is multiple, Helicobacter pylori infection is strongly associated with the development of gastric cancer. Methodology: A review of professional international journals and public health publications related to the association of Helicobacter pylori infection and gastric cancer Topic: As early as 1994, the International Agency for Research on Cancer and the World Health Organization identified Helicobacter pylori as a type I carcinogen in humans, although the exact mechanism of carcinogenesis has not yet been clearly established. Carcinogenesis is also influenced by environmental factors, as well as genetic diversity, which can lead to different inflammatory responses and thus affect the clinical outcome of the disease. Chronic gastritis caused by Helicobacter pylori infection is the strongest known risk factor for the development of adenocarcinoma of the distal part of the stomach. The effect of eradicating Helicobacter pylori infection is seen in the reduced risk of gastric cancer, but several therapeutic attempts to prevent the development of gastric tumors by eradicating Helicobacter pylori infection have yielded minimal results. In an attempt to elucidate this problem in high-risk populations, researchers began conducting prospective randomized, double-blind population studies. The results of previous studies have highlighted the importance of long-term and careful monitoring of patients after eradication therapy, but there are still multiple deviations ("enigmas") that call into question the cause-effect relationship between H. pylori and gastric cancer. Conclusions: It has been established that the eradication of Helicobacter pylori, in order to prevent gastric cancer, is effective only when it is carried out before the development of premalignant changes: atrophy, metaplasia, and dysplasia of the gastric mucosa. In addition , the significant treatment efficacy observed in younger patients suggests the need to eradicate Helicobacter pylori infection as early as possible.